Εκκλησιαστικά ασημικά από την Κωνσταντινούπολη και ο πατριαρχικός θρόνος του Ιερεμία Β' - Μπαλλιάν, Άννα (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1988)
16th century Orthodox liturgical silver displays a hybrid Christian-Islamic character exemplified in the persistence of the Byzantine iconographie tradition, in the use of western European shapes and techniques, and in the adoption of Ottoman decorative styles. Two characteristic examples of this hybrid style are a bowl stamped with the tugra of Bayezid the II (fig. 1) and a jug with animal decoration and christological symbolism (fig. 8). Both can be attributed to the Balkans or at any rate to a Christian tradition which was formative for Ottoman silverware. To the same tradition we can ascribe two more silver objects, a chalice (fig. 4) donated by Patriarch Theoleptos the II (1585-1587), and an enamelled bowl (fig. 6) inscribed with the name of the Metropolitan of Euripos, Laurentios (manufactured in 1580 or 1587). Their particular interest, however, lies in that they can be securely attributed to Greek craftmanship in Constantinople and reflect the cultural milieu in which they were produced —the Oecumenical Patriarchate. In the second half of the 16th century, the Oecumenical Patriarchate was in the process of realising and asserting its secular power towards both the Ottoman authorities and its Christian flock. In this process Patriarch Jeremia II played the most important role. His restoration of the patriarchal church and premises was an ambitious project worthy of an Oriental potentate. Today, only his patriarchal throne survives (fig. 8). Dated 1577, it has a Byzantine shape, Ottoman inlaid decorative designs and long inscriptions in verse praising with Byzantine eloquence the secular powers of the Patriarch.